TAJWID AL- QUR’AN : KAJIAN HUKUM, MACAM-MACAM, DAN PENERAPAN DASAR - Faturrahman, Ferdi; Nur Fadhilah , Atikah; Ilhamul Hafidz, Muhammad; Sawitri, Riska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Tajweed constitutes a systematically structured scholarly discipline governing the correct and precise method of Qur'anic recitation. This study aims to examine the foundational concepts of tajweed and its recitation rules through a library research methodology, drawing upon classical Islamic texts and contemporary Islamic education literature. The discussion centers on three principal themes: first, the definition and legal standing of tajweed; second, the rules governing nun sakinah/tanwin and mim sakinah; and third, the rules of mad, qalqalah, ghunnah, tafkhim, and tarqiq. Each rule is analyzed comprehensively, encompassing operational definitions, applied examples, implementation procedures, commonly occurring errors, and pedagogicalimplications.This study affirms that reciting the Qur'an in accordance with tajweed holds the status of an individual obligation (fardhu'ain), rendering mastery of these rules an essential foundation in Qur'anic education. Educators are recommended to prioritize oral practice through the talaqqi method in the learning process.